Toxicological survey of African medicinal plants - Kuete, Victor (Elsevier insights., 2014)
Toxicological Survey of African Medicinal Plants provides a detailed overview of toxicological studies relating to traditionally used medicinal plants in Africa, with special emphasis on the methodologies and tools used for data collection and interpretation. The book considers the physical parameters of these plants and their effect upon various areas of the body and human health, including chapters dedicated to genotoxicity, hepatotoxicity, nephrotoxicity, cardiotoxicity, neurotoxicity, and specific organs and systems. Following this discussion of the effects of medicinal p.